Manual de procesos administrativos para mejorar el desempeño laboral de la Asociación de Agricultores progresista Loma Alta, Santa Elena. - Tomalá Torres, Félix Antonio (2017)
The research work "Manual of administrative processes to improve the labor performance of the Association of Progressive Farmers Loma Alta, Santa Elena" here presented was carried out in the Commune Loma Alta, located northwest of the Provincia of Santa Elena, in the Parroquia Colonche, it is aimed at the Progressive Farmers Association "Loma Alta" as direct beneficiaries of the proposal. Through surveys conducted on farmers, it was determined that the association lacks a manual about administrative processes, they do not have tools that favor the work performance, there is ignorance of the functions that they play within the Organization. From this study arises the need to implement a manual of administrative processes, which contributes to the solution of the problem posed. Fundamental aspects were analyzed of the community and the association, as well as the administrative processes, the work performance, among others; each one of these is based on bibliographic references in the literature review. For the construction of this investigative work, field research was used to determine the social group contributing with important information through the application of research techniques. The manual will help the association to improve the work performance of its members, with this tool there will be a greater control in the production process and the directive is clear the role that it deserves to assume responsibly its functions and Teamwork will achieve the goals of the association. Key words: Administrative processes, work performance, association.